Remote Sensing of Impervious Surfaces - Weng, Qihao (Taylor & Francis Series in Remote Sensing Applications, 2008)
Expertly written and edited, this book focuses on mapping, data extraction, and modeling techniques specific to remote sensing of impervious surfaces. It introduces remote sensing digital image processing techniques for estimating and mapping impervious surfaces in urban and rural areas. Presenting modeling tools and algorithms for data extraction and analysis, the book explains how to differentiate roads, roofs, and other manmade structures from remotely sensed images for individual analysis. The final chapters discuss case studies within significant application areas of impervious surface data in watershed management, environmental conservation, and urban and regional planning.